2020
DOI: 10.1186/s13195-019-0578-9
|View full text |Cite|
|
Sign up to set email alerts
|

Nrf2 activation through the PI3K/GSK-3 axis protects neuronal cells from Aβ-mediated oxidative and metabolic damage

Abstract: Background: Mounting evidence points to a crucial role of amyloid-β (Aβ) in the pathophysiology of Alzheimer's disease (AD), a disorder in which brain glucose hypometabolism, downregulation of central elements of phosphorylation pathways, reduced ATP levels, and enhanced oxidative damage coexist, and sometimes precede, synaptic alterations and clinical manifestations. Since the brain has limited energy storage capacity, mitochondria play essential roles in maintaining the high levels of energy demand, but, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 122 publications
4
34
0
1
Order By: Relevance
“…δ-tocotrienol binds to the estrogen receptor β and activates PI3K/Akt signaling pathways including phosphorylation of protein kinase B (PKB, Akt) and extracellular signal-regulated kinase (ERK) 1/2 [ 128 , 168 ]. Akt activates Nrf2 [ 169 , 170 ], and Nrf2-mediated upregulation of antioxidant and prosurvival genes is an important mechanism for the neuroprotective properties of many antioxidant nutrients [ 171 , 172 , 173 ]. Clinical studies with PD patients show that higher consumption of dietary vitamin E is inversely related to PD occurrence [ 157 , 164 , 174 , 175 ].…”
Section: Neuroprotective Dietary Antioxidantsmentioning
confidence: 99%
“…δ-tocotrienol binds to the estrogen receptor β and activates PI3K/Akt signaling pathways including phosphorylation of protein kinase B (PKB, Akt) and extracellular signal-regulated kinase (ERK) 1/2 [ 128 , 168 ]. Akt activates Nrf2 [ 169 , 170 ], and Nrf2-mediated upregulation of antioxidant and prosurvival genes is an important mechanism for the neuroprotective properties of many antioxidant nutrients [ 171 , 172 , 173 ]. Clinical studies with PD patients show that higher consumption of dietary vitamin E is inversely related to PD occurrence [ 157 , 164 , 174 , 175 ].…”
Section: Neuroprotective Dietary Antioxidantsmentioning
confidence: 99%
“…Some studies reported the potential role of Aβ monomers as antioxidants, depending on the metal ion concentration in vitro [ 49 , 50 ]. In contrast, other studies showed that oligomeric Aβ, the dominant form in patients with AD, promotes ROS production in cooperation with metal ions in vitro and in vivo [ 51 , 52 , 53 , 54 ]. In addition, inhibition of the γ-secretase activity was reported to reduce the levels of ROS and oxidize proteins, and to enhance resistance to oxidative stress [ 55 ].…”
Section: Dysregulation Of Redox Homeostasis In Neurodegenerative Diseasesmentioning
confidence: 96%
“…In addition, inhibition of the γ-secretase activity was reported to reduce the levels of ROS and oxidize proteins, and to enhance resistance to oxidative stress [ 55 ]. Aβ activates NADPH oxidase and interferes with Ca 2+ homeostasis and mitochondrial membrane potential, leading to impaired ROS homeostasis [ 53 , 56 , 57 , 58 ]. Tau neurofibrillary tangles, which contain oxidized molecules, also produce ROS by interacting with Cu 2+ , which in turn increases the formation of tau aggregates [ 59 ].…”
Section: Dysregulation Of Redox Homeostasis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…At present, the most accepted theory attributes a major role to the aberrant production and accumulation of protein aggregates, including different amyloid‐β (Aβ) peptides (Ishida et al., 2020). However, the exact cellular and molecular mechanisms underlying this disorder remain unclear (Sotolongo, Ghiso, & Rostagno, 2020) The current medications for AD are mainly cholinesterase inhibitors (including donepezil, galantamine, rivastigmine) and N‐methyl‐D‐receptor antagonists (memantine; Rygiel, 2016), which can only alleviate symptoms. There are still no effective treatments to prevent, halt, or reverse AD (Huang & Mucke, 2012).…”
Section: Introductionmentioning
confidence: 99%